Implementation of 5E Plus Learning Model on Energy Subject Matter to Improve Students’ Argumentation Skills - Wikara, B.; Sutarno, S.; Suranto, S.; Sajidan, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Argumentation skills consist of 2 elements: skills to construct arguments and implement them. However, some studies show that students’ argumentation skills were low. This study proposed the 5E Plus learning model to improve students’ argumentation skills. The model consists of an element named Enliven and six syntaxes: Orientation, Engagement, Exploration, Explanation, Elaboration, and Evaluation. This study aimed to investigate the effectiveness of the 5E Plus learning model in improving students’ argumentation skills. This study used Energy subject matter (which consisted of 3 topics, Mechanical, Heat, and Electrical Energy). The study’s sample consisted of 40 1st semester college students from the Natural Science department and was taken randomly. We used One-Group Pretest-Posttest as a research design and collected data using an argumentation skills test. The data was examined using an Independent sample t-test to determine the effectiveness of the 5E Plus learning model. The results were: 1) the 5E Plus learning model was effective for improving students’ argumentation skills, 2) All components of students’ argumentation skills were successfully improved, which warrant experienced the highest improvement, 3) Students’ argumentation skills in all three topics were successfully improved, which in Mechanical Energy topic the skills experienced the highest improvement.